DIBENTUKNYA NEGARA KOLONIAL DI SULAWESI BAGIAN SELATAN DI ABAD KE-19 - Dias Pradadimara (Fakultas Ilmu Budaya universitas Hasanuddin, 2017)
This contribution is an attempt to look at events which constituted as the early founding of the colonial state in southern Sulawesi in the 19th century, especially after 1824. These events were parts of a long historical process where the colonial state was formed and at the same time resisted by local power holders. The main tools in administrative reorganization and colonial control in 1824 were the Nieuw Organisatie and the renewed Bungaya Treaty. After 1850, rapid trade growththrough Makassar, the conquest of Bone, and reorganization of the judicial system all contributed to the stabilization of the new colonial state.